DESIGN OF CASH REGISTER SYSTEM AT SMALL AND MEDIUM ENTERPRISE IN CHINA - Rachman, Windy Atmawardani (Universitas Gunadarma, 2014)
Development of Accounting Information Systems (it present has an important roletowards the progress ofthe business world. Not only big companies need informationsystem, small and medium enterprises also require accounting information system.The main use ofcash register system is to make calculation process and producingreports easier. Hua Qin Minimarket have been using the application of acomputer in the process of calculation but the cash register system still haveweaknesses, such as could not produce inventory reports, sales reports and evidenceofpayment. The author improves the system by making a new cash register system.Design of this system begins with designing a system by using dataflow diagramand flowchart. The programming language used to create this cash register systemis Visual Basic 6.0. Database programming used Microsoft Access 2007 and CrystalReport is used to create reports. Design of cash register system used inventorydata and sales transaction data to produce information such as inventory reportand sales report consisting ofdaily sales report, monthly sales report and annualsales report to be given to the General Manager and evidence ofpayment to begiven to the customers. Improvement of this cash register system has not beenimplemented because ofthe time limitations ofthe author in the research. Hopefully,design of this cash register system can minimize the weaknesses in the presentcash register system, such as that can produce the required reports precisely andaccurately, can improve the performance ofHua Qin Minimarket to be better andcan assist management in decision making.